1989
DOI: 10.1111/j.1432-1033.1989.tb14551.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stimulation of rat skeletal muscle induces coordinate increases in mitochondrial and nuclear mRNAs of cytochrome‐c‐oxidase subunits

Abstract: Fast-twitch tibialis anterior muscle of the rat was subjected to chronic low-frequency (10 Hz, 10 h daily) nerve stimulation in order to investigate the time course of changes in cytochrome-c-oxidase activity, as well as in tissue levels of specific mitochondrially and nuclear-encoded, cytochrome-c-oxidase-subunit mRNAs. Chronic stimulation induced a progressive increase in cytochrome-c-oxidase activity which was threefold elevated after 35 days. A similar increase was recorded for citrate-synthase activity. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(104 citation statements)
references
References 30 publications
7
96
1
Order By: Relevance
“…Support for a transcriptional coordination between nuclear and mitochondrial genes has been provided by numerous reports (Hood et al 1989;Gagnon et al 1991;Van den Bogert et al 1993;Connor et al 1996;Heddi et al 1999). However, data from analysis of changes in mitochondrial transcription in response to thyroid hormones (Enriquez et al 1999) as well as data from reporter gene activity (Sewards et al 1994) have indicated that mitochondrial and nuclear transcription systems operate independently.…”
Section: Discussionmentioning
confidence: 99%
“…Support for a transcriptional coordination between nuclear and mitochondrial genes has been provided by numerous reports (Hood et al 1989;Gagnon et al 1991;Van den Bogert et al 1993;Connor et al 1996;Heddi et al 1999). However, data from analysis of changes in mitochondrial transcription in response to thyroid hormones (Enriquez et al 1999) as well as data from reporter gene activity (Sewards et al 1994) have indicated that mitochondrial and nuclear transcription systems operate independently.…”
Section: Discussionmentioning
confidence: 99%
“…We report here that mtDNA does turn over independent of somatic growth in hindlimb and cardiac muscle, that human platelets represent a highly accessible tissue, and that the method is well tolerated in people as well as rodents. Many possible research questions can be addressed by this approach, including inborn errors of mtDNA or mitochondrial biogenesis, assessment of aerobic fitness or aerobic demand on tissues, and toxicities of antiretroviral drugs (9,11,17,20,21). Future applications include isolation of mtDNA from other tissues, such as adipose or human skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…RNA (10 -30 g) was then electrophoresed on 1% agarose gels containing 0.02% formaldehyde, transferred, and fixed to nylon membranes (Hybond N; Amersham Pharmacia Biotech, Mississauga, ON, Canada). The membranes were then prehybridized and hybridized overnight at 42°C with a 32 P-labeled cDNA probe encoding either COX III (20) or COX Vb. The cDNA probes were radiolabeled with [␣-32 P]dCTP and a random primer labeling kit (New England Biolabs, Beverly, MA).…”
Section: Methodsmentioning
confidence: 99%
“…COX regulation is therefore a useful indicator of mitochondrial biogenesis, since a functional holoenzyme requires the coordination of both of these genomes. Although the coordinate induction of COX subunit mRNA derived from the nuclear and mitochondrial genomes is well established with contractile activity (20,33), this does not appear to be the case in response to altered T 3 status in which nuclear-encoded mRNAs appear to remain unchanged (40) or change with different kinetics (44) from mtDNA-encoded transcripts. Therefore, the purposes of our study were 1) to determine the extent of coordination between the nuclear and mitochondrial genomes at the protein level of expression, 2) to compare this to functional measures of holoenzyme activity, 3) to examine the role of transcriptional activation in the T 3 -induced response, and 4) to compare our measure of transcriptional activation with the expression of TR isoforms in tissues that are known to be responsive to T 3 .…”
mentioning
confidence: 99%